Algoritmo MPPT para sistema de geração de energia eólica de pequeno porte com PMSG - Duarte, Odilio de Souza (2017)
This work aims to develop an MPPT algorithm to optimize the energy extracted from the wind by a permanent magnet synchronous generator (PMSG) in a wind energy generation system with variable speed. The algorithm proposes to find the point of maximum power extraction without requiring a wind speed measurement system, nor of the constructive characteristics of the wind turbine that describes its power coefficient (CP). The basis for the development of the MPPT algorithm lies in combining the OTC (Optimal Torque Control) and HCS (Hill Climb Searching) methods. With the HCS method, the algorithm traces the MPPT and sets the gain value here called Kotm. This gain indirectly carries constructive characteristics of the wind turbine related to power extraction, being used to generate the torque reference to the control system by the OTC Method. Experimental results are presented with the aid of a test platform, using a PMSG of 5 kW with 36 poles.